The ethics of publishing in medical journals. (September 2021) - Isaacs, David; Elliot, Chris; Kilham, Henry; Preisz, Anne
Abstract: Ethics has been defined as the way we ought to behave. Medical publishing essentially exists to broadcast current and new medical knowledge to aid in the practice of medicine. In this review article we consider many of the aspects of medical publishing with regard to 'what we ought to do' and, equally, 'what we ought not to do' from the perspective of various ethical frameworks. Although ethics is not the law or a set of rules, nor a code of conduct, an ethical lens can be useful when developing good general guidelines for medical publishing.